2011
DOI: 10.1007/s10230-011-0153-5
|View full text |Cite
|
Sign up to set email alerts
|

The Applications of Satellite Based Remote Sensing Techniques in the Hydrological Assessment of Mine Water Supply and Management Systems

Abstract: Mineral resources are often discovered in remote or mountainous areas where long-term hydrological records are either absent or limited. Satellite-based remote sensing techniques can provide indirect observations of phenomena of interest, such as rainfall depth, snow cover, evapotranspiration, and changes in groundwater levels. Quality and applicability of the data are limited by the spatial, spectral, and temporal resolution of images. Other limitations may arise from the algorithms used to interpret the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…At present, means to determine river runoff directly from RS-data are lacking. However, earlier studies have shown that the use of RS-data as input in distributed hydrological models can enhance our modeling capabilities of surface runoff (Immerzeel et al, 2008;Liu et al, 2012;Qin et al, 2008;Schultz, 1996;Shelp et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…At present, means to determine river runoff directly from RS-data are lacking. However, earlier studies have shown that the use of RS-data as input in distributed hydrological models can enhance our modeling capabilities of surface runoff (Immerzeel et al, 2008;Liu et al, 2012;Qin et al, 2008;Schultz, 1996;Shelp et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…For example, in a study conducted in semi-arid Botswana, a combination of surface, ground, and waste water, and a variety of harvesting and delivery techniques were used to overcome general water scarcity and periods of drought (Rahm et al 2006). Various methods can be used to assess the suitability of water resources, but as stated by Shelp et al (2011), understanding the local water resources is essential.…”
Section: Introductionmentioning
confidence: 99%